Olfactory mucosa in herpes simplex encephalitis. Issue 11 (November 1979) - Twomey, J A; Barker, C M; Robinson, G; Howell, D A
Abstract : The olfactory mucosa was examined in three patients dying from herpes simplex encephalitis. It showed changes attributed to infection by the herpes simplex virus. It is suggested that in some patients encephalitis may be a complication of infection of the olfactory mucosa.